Workers, New Orleans, and the global shipbuilding regime. (1st October 2012) - ,
Abstract : This article focuses on what happens to local labour markets when global employers relocate, using the example of Avondale shipyard at the edge of New Orleans, which provides almost 5, 000 good jobs but is currently threatened with shutdown. Drawing on surveys, focus groups, and interviews with Avondale workers conducted during the last six months of 2011, it demonstrates the high levels of human and social capital accumulated by Avondale workers and their resulting contribution to the civic life of their communities and argues that the loss of these shipyard jobs will have broad ramifications for the wider New Orleans community. It concludes that the breakdown of the workplace-based organisations of these workers will lead to a loss of civic engagement that threatens the basis of democracy as traditionally conceived in the USA. Further, it explores the nature of the global shipbuilding regime, and sketches an out an alternative vision for the future of the yard, based on mobilising the skills and social capital of the existing workforce.